2014
DOI: 10.5901/mjss.2014.v5n27p1712
|View full text |Cite
|
Sign up to set email alerts
|

Stock Return Response to Monetary and Fiscal Policy Interaction in Singapore

Abstract: The objective of the study is to examine the monetary and fiscal policies '

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 141 publications
(145 reference statements)
0
2
0
Order By: Relevance
“…On the contrary, for net commodity importers, decrease of commodity prices is an important impulse for domestic economy through lower level of energy prices. According to the authors (Ali, Zaman, Ziaei, Anuar ,2014), the wealth effect of house prices has positive influence on the stock market, but house prices impact is very weak on stock returns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the contrary, for net commodity importers, decrease of commodity prices is an important impulse for domestic economy through lower level of energy prices. According to the authors (Ali, Zaman, Ziaei, Anuar ,2014), the wealth effect of house prices has positive influence on the stock market, but house prices impact is very weak on stock returns.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is significant for researchers to find more factors effecting on stock market. For the case of Singapore, Ghulam Ali et al (2014) revealed the significance of researching this subject. The reason was that policy makers and investors would have a glance at the financial market in the future as the changes in monetary policy and fiscal policy were implemented.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies on fiscal policy and stock market performance as well as stock market returns have been undertaken by various researchers in Nigeria (see Prukumpai & Sethapramote, 2019;Nwaogwugwu, 2018;Eyo, 2018;Perveen & Rahman, 2018;Onyema, 2017;Kuncoro, 2017;Anghelache, Jakova & Oanea, 2016;Ogbulu, Torbira & Umezinwa, 2015;Ali, Zaman Ziaei & Anuar, 2014;Mutulis & Olweny, 2018;Gowriah, Seetanah, John & Keshav, 2014;Cheng & Sun, 2013;Hsing, 2013;Bekhet & Othman, 2012;Osamwonyi & Evbayiro-Osagie, 2012). However, about stock market development using the World Bank (2013) indices of measuring development in the stock market (stock market capitalization ratio, the value of stock traded ratio, and turnover ratio) have often been ignored in studies conducted in Nigeria.…”
Section: Introductionmentioning
confidence: 99%